Perceptions of specialists in the public sector, on the role and value of family medicine - Rihangwele Mukhinindi; Andrew J. Ross (South African Family Practice)
Background: Family medicine (FM) is often perceived to be a ‘lesser’ speciality compared with other disciplines, despite its importance as a generalist discipline in the healthcare system. Family physicians (FPs) provide comprehensive care at the district level and act as a gatekeeper for patient’s upward referral to other specialists. This study aimed to explore the perceptions of healthcare specialists other than FPs involved in registrar training regarding FM at the University of KwaZulu-Natal, South Africa (SA).